2008
DOI: 10.1093/ndt/gfm888
|View full text |Cite
|
Sign up to set email alerts
|

The clinical evaluation of low-dose heparin in haemodialysis: a prospective study using the heparin-coated AN69 ST membrane

Abstract: The use of the heparin-coated AN69 ST membrane allows a 50% reduction of standard doses of nonfractionated heparin administration for routine haemo- dialysis without increasing the risk of massive clotting of the extracorporeal circuit. This result needs confirmation since massive clotting questions clinical practice and is team dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…Furthermore, there are some patients at high risk of bleeding, where heparin cannot be used. The recent improvement and innovation in dialysis membranes have yielded high-flux membranes graft-ed with unfractionated heparin that can be used to avoid or reduce the exposure to systemic heparin [71].…”
Section: Compatible Hemodialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are some patients at high risk of bleeding, where heparin cannot be used. The recent improvement and innovation in dialysis membranes have yielded high-flux membranes graft-ed with unfractionated heparin that can be used to avoid or reduce the exposure to systemic heparin [71].…”
Section: Compatible Hemodialysismentioning
confidence: 99%
“…Different studies have documented the efficiency of high-flux dialyzers in removing β 2 -M from the circulation of patients on dialysis, which has been associated with clinical and radiological improvement of carpal tunnel syndrome and dialysis-related amyloidosis [78]. In addition, high-flux HD has been shown to be superior to peritoneal dialysis in clearing β 2 -M and the protein-bound middle molecule p-cresol [71]. Furthermore, observational studies have documented the improvement of survival rates of patients on high-flux-dialyzers when compared with those on low-flux dialyzers [9,[79][80][81][82].…”
Section: High-flux Hemodialysismentioning
confidence: 99%
“…Zhu et al [6], Jiang et al [7] and Huang et al [8,9] also improved blood compatibilities of the poly(vinylidene fluoride), polyethylene (PE) and PSF membranes by covalent attachment of heparin [6][7][8][9]. In vivo tests carried out with commercial hemodialysis membranes, AN69 ST, HEMOPHAN and EVODIAL showed that it is possible to reduce systemic administration of heparin through its immobilization on these membranes [10][11][12][13][14][15]. On the other hand, one clinical study reported that heparin coated AN69 ST membrane does not reduce clotting during hemodialysis when compared to a conventional PSF filter [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used approach is to mimic endothelial cell layer by heparin immobilization. The beneficiary effect of heparin coatings on the membranes has been reported by many authors both in vitro [1][2][3][4][5][6][7][8][9] and in vivo [10][11][12][13][14][15]. For example, Cheung et al [1] observed that complement activation induced by hemodialysis can be modulated with heparin immobilized cellulose acetate membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation